High performance supercapattery with rGO/TiO2 nanocomposites anode and activated carbon cathode - Heng I.; Low F.W.; Lai C.W.; Juan J.C.; Amin N.; Tiong S.K. (Elsevier Ltd, 2023)
Activated carbon; Anodes; Cathodes; Charge transfer; Crystallinity; Electric discharges; Graphene; Hybrid materials; Life cycle; Nanocrystals; Oxide minerals; Supercapacitor; Titanium dioxide; Charge transfer resistance; Charge-discharge cycle; Electrochemical performance; High specific capacity; Hydrothermal methods; Hydrothermal techniques; rGO/TiO2; Supercapattery; Reduced Graphene Oxide